A qualitative study of perceived social barriers to care for eating disorders: Perspectives from ethnically diverse health care consumers - Becker, Anne E (Wiley Subscription Services, Inc., A Wiley Company, 2010)
OBJECTIVE: The study aim was to identify and describe health consumer perspectives on social barriers to care for eating disorders in an ethnically diverse sample. METHOD: We conducted an exploratory secondary analysis of qualitative data comprising transcripts from semi-structured interviews with past and prospective consumers of eating disorder treatment (n = 32). Transcripts were inputted into NVivo 8 for coding, sorting, and quantifying thematic content of interest within strata defined by ethnic minority and non-minority participants. We then examined the influence of key social barriers—including stigma and social stereotypes—on perceived impact on care. RESULTS: The majority of respondents (78%) endorsed at least one social barrier to care for an eating or weight concern. Perceived stigma (or shame) and social stereotyping—identified both within social networks and among clinicians—had adversely impacted care for 59% and 19% of respondents, respectively. DISCUSSION: Social barriers to care for eating and weight related concerns may be prevalent in the U.S. and impact both ethnic minority and non-minority health care consumers. © 2009 by Wiley Periodicals, Inc. (Int J Eat Disord 2010;)